Postpartum Depression - Not a gender-specific psychiatric illness - Aimen Fatimah kidwai (ziauddin University, 2024)
Postpartum depression (PPD), a common psychiatric complication of pregnancy, may be defined as persistent sad behavior, melancholic mood, anxiety, and lethargy within a year after childbirth. PPD is considered an exclusively female psychiatric illness, however, recent research shows that PPD affects males too. A meta-analysis published recently reveals that around 10% of new fathers experience depressive symptoms around the time of their child's birth, especially after 3 to 6 months of having a baby.